The first record of Sona sea catfish Pseudosciades sona (Hamilton 1822) in Sabah, Malaysian Borneo, on the basis of morphological and molecular data - B. Mabel Manjaji-Matsumoto; S. Nasihin-Seth; Nazia A.K (Borneo Marine Research Institute, 2024)
The Sona Sea Catfish Pseudosciades sona is widely distributed across the Indo-West Pacific, including Malaysia. In this paper, we report the first record of the species from Sabah, based on morphological and molecular data. The single specimen of Pseudosciades sona was obtained during a field survey, from the fish market in Beluran, Sabah. The DNA of the specimen has been sequenced and data was published in elsewhere. The species is diagnosed by a combination of morphometric characteristics, including 10–12 pectoral-fin rays, long head (27.59%–31.85% of SL), long snout (28.89%–35.86% of HL), wide mouth (58.04%–65.72% of HL), eye diameter (12.90%–15.75% of HL), distance between below the eye to the bottom of the head (18.95%–24.57% of HL), distance between behind the eye and the margin of operculum (55.75%–60.32% of HL), bony interorbital width (53.67%–60.03% of HL), long bases of dorsal-fin (5.21%–6.18% of SL), anal-fin (13.12%–16.64% of SL), pectoral-fin (5.21%–6.18% of SL), and pelvic-fin (4.14%–5.34% of SL). This paper describes the morphological features of this species, with a brief discussion on catfish conservation and its significance as a fishery resource in Malaysia.